One‐Step Synthesis of Fluorescent Carbon Dots for Bio‐Labeling Assay. Issue 1 (19th December 2018) - Das, Poushali; Bose, Madhuparna; Das, Amit Kumar; Banerjee, Susanta; Das, Narayan Chandra
Abstract : Luminescent carbon dots, a newcomer in the domain of nanolights and nanomaterials have been studied extensively since past few years due to their fascinating properties of sensor design, biocompatibility, cell tracking, or fluorescence based live cell assays, medical diagnosis, photocatalysts, and also being potential building blocks for nanodevices. In this study, one‐pot green synthesis of water dispersible fluorescent carbon dots have been synthesized by using roasted gram shells. The structural and optical properties of the as‐prepared carbon dots are characterized by TEM, FTIR, UV‐vis absorption, photoluminescence spectra. The carbon dots showed greenish blue fluorescence under UV irradiation, excitation dependent emission, upconverted emission, high pH tolerance, and good biocompatibility. The carbon dots labeled Escherichia coli ( E. coli ) unveiled multicolor emission behavior under different excitation wavelength. These carbon dots showed their superiority with respect to commercially available synthetic dyes which have severe limitations including photobleaching effect, high cost, etc. The incorporation of carbon dots in the bacterial culture medium does not show any kind of growth delay of the bacterium up to 400 mg mL −1 . The goal is to establish this carbon dots in bio‐labeling assay with its physicochemical features (small particle size, high luminescence efficiency, good biocompatibility, low toxicity) against various environments such as wide range of pH, high ionic medium. Concisely, this work bestows an innovative aspect to the commercialization of carbon dots as a potent alternative to synthetic organic dyes for multicolor emitting probes for cell‐labeling gram negative bacteria E. coli .